Using microphone arrays to investigate microhabitat selection by declining breeding birds: Oroignal. (7th November 2019) - Ethier, Jeffrey P.; Wilson, David R.
Abstract : Understanding the microhabitat preferences of animals can help managers to develop better conservation and recovery strategies but this is challenging. Traditional methods are limited by cost, accuracy and human resources. In this study, we investigated avian microhabitat preferences using microphone arrays that are capable of accurately locating vocalizing birds. Our objective was to identify the microhabitat associations of two common species in steep population decline, the Boreal Chickadee Poecile hudsonicus and the Cape May Warbler Setophaga tigrina . We deployed 68 eight‐channel arrays at random locations in Labrador, Canada, during the 2016 avian breeding season. We returned in 2017 to the 18 array locations where the target species had been detected the previous year and characterized the microhabitat at the exact locations where they had been detected. We also characterized the microhabitat at randomly determined control locations. Results show that Boreal Chickadees select trees with greater diameter‐at‐breast‐height that are surrounded by greater stem density. We did not find evidence that Cape May Warblers exhibit microhabitat selection during song production. The study shows that microphone arrays are an effective tool for identifying preferred microhabitat that could be incorporated into future conservation or recovery strategies.